Smallholder value chains as complex adaptive systems: a conceptual framework - Orr, A.; Donovan, J.; Stoian, D. (Emerald Publishing Limited, 2018)
Smallholder value chains are dynamic, changing over time in sudden, unpredictable ways as they adapt to shocks. Understanding these dynamics and adaptation is essential for these chains to remain competitive in turbulent markets. Many guides to value chain development, though they focus welcome attention on snapshots of current structure and performance, pay limited attention to the dynamic forces affecting these chains or to adaptation. The paper aims to discuss these issues.